2015
DOI: 10.1126/scitranslmed.aaa5079
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic therapy overcomes treatment resistance in T cell prolymphocytic leukemia

Abstract: T-cell prolymphocytic leukemia (T-PLL) is a rare, mature T-cell neoplasm with distinct features and an aggressive clinical course. Early relapse and short overall survival are commonplace. Use of the monoclonal anti-CD52 antibody alemtuzumab has improved the rate of complete remission and duration of response to over 50% and between 6–12 months, respectively. Despite this advance, without an allogeneic transplant, resistant relapse is inevitable. We report complete (7) and partial (1) remissions in eight patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 60 publications
3
34
2
Order By: Relevance
“…Importantly, HDAC inhibitors (vorinostat, belinostat, romidepsin) are FDA approved for the treatment of nodal and cutaneous peripheral T cell lymphomas (PTCL, CTCL). In a series of eight relapsed T-PLL patients, the combination of HDAC inhibitors with cladribine, a purine analog with epigenetic activity, enhanced the anti-leukemic activity of alemtuzumab and overcame previous treatment resistance towards this antibody as shown by responses in all treated patients (7 of 8 achieved a CR) [52]. Furthermore, an induction of CD30 expression after treatment with this combination was reported therein.…”
Section: Epigenetic Modulationmentioning
confidence: 82%
“…Importantly, HDAC inhibitors (vorinostat, belinostat, romidepsin) are FDA approved for the treatment of nodal and cutaneous peripheral T cell lymphomas (PTCL, CTCL). In a series of eight relapsed T-PLL patients, the combination of HDAC inhibitors with cladribine, a purine analog with epigenetic activity, enhanced the anti-leukemic activity of alemtuzumab and overcame previous treatment resistance towards this antibody as shown by responses in all treated patients (7 of 8 achieved a CR) [52]. Furthermore, an induction of CD30 expression after treatment with this combination was reported therein.…”
Section: Epigenetic Modulationmentioning
confidence: 82%
“…In T‐prolymphocytic leukaemia (T‐PLL), treatment with cladribine has been shown to induce CD30 expression, enabling successful use of anti‐CD30 directed therapy. This phenomenon appeared to be T‐PLL specific and was not appreciated in MCL (Hasanali et al , ). However, it does suggest that cladribine has the potential to modify the expression of potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, preclinical in vivo work has suggested that restoration of MHC-I expression by modulation of epigenetic markers, such as inhibitors of DNA methyltransferase (DNMT) or histone deacetylase (HDAC), constitutes an attractive approach to be used as a complement to TCR-modified T cell administration for successful tumour eradication [126][127][128] , even in the context of cancers that are resistant to immune checkpoint blockade 129 . A few clinical trials have been performed evaluating the effects of combining epigenetic modulation with vaccine/antibody/cytokine-based immunotherapy, which rendered promising results [130][131][132] . However, the feasibility/benefit of this approach in the context of clinical ACT using remains to be determined.…”
Section: Mhc-i Downregulationmentioning
confidence: 99%